Skin Temperature Measurement Using Contact Thermometry: A Systematic Review of Setup Variables and Their Effects on Measured Values - MacRae, Braid A.; Annaheim, Simon; Spengler, Christina M.; Rossi, René M. (Frontiers in Physiology, 2018)
Background. Skin temperature (Tskin) is commonly measured using Tskin sensors affixed directly to the skin surface, although the influence of setup variables on the measured outcome requires clarification. Objectives. The two distinct objectives of this systematic review were 1) to examine measurements from contact Tskin sensors considering equilibrium temperature and temperature disturbance, sensor attachments, pressure, environmental temperature, and sensor type, and 2) to characterise the contact Tskin sensors used, conditions of use, and subsequent reporting in studies investigating sports, exercise, and other physical activity. Data sources and study selection. For the measurement comparison objective, Ovid Medline and Scopus were used (1960 to July 2016) and studies comparing contact Tskin sensor measurements in vivo or using appropriate physical models were included. For the survey of use, Ovid Medline was used (2011 to July 2016) and studies using contact temperature sensors for the measurement of human Tskin in vivo during sport, exercise, and other physical activity were included. Study appraisal and synthesis methods. For measurement comparisons, assessments of risk of bias were made according to an adapted version of the Cochrane Collaboration’s risk of bias tool. Comparisons of temperature measurements were expressed, where possible, as mean difference and 95% limits of agreement (LoA). Meta-analyses were not performed due to the lack of a common reference condition. For the survey of use, extracted information was summarised in text and tabular form. Results. For measurement comparisons, 21 studies were included. Results from these studies indicated minor (<0.5°C) to practically meaningful (>0.5°C) measurement bias within the subgroups of attachment type, applied pressure, environmental conditions, and sensor type. The 95% LoA were often within 1.0°C for in vivo studies and 0.5°C for physical models. For the survey of use, 172 studies were included. Details about Tskin sensor setup were often poorly reported and, from those reporting setup information, it was evident that setups widely varied in terms of type of sensors, attachments, and locations used. Conclusions. Setup variables and conditions of use can influence the measured temperature from contact Tskin sensors and thus key setup variables need to be appropriately considered and consistently reported.